Bleomycin-induced pulmonary fibrosis is attenuated by an antibody against KL-6. (1st August 2013) - Xu, Ling; Yang, Danrong; Zhu, Songlei; Gu, Jie; Ding, Fengming; Bian, Wei; Rong, Zhaohui; Shen, Ce
ABSTRACT: Background : Elevated levels of KL-6 are reported in the serum and/or bronchoalveolar lavage fluid (BALF) of patients with interstitial lung disease (ILD) and are useful to estimate the severity and prognosis of the disease. However, whether the anti-KL-6 antibody could attenuate pulmonary fibrosis remains unclear. Objectives : This study aims to investigate the therapeutic effects and mechanisms of anti-KL-6 antibody on bleomycin-induced pulmonary fibrosis. Methods : A mouse model of pulmonary fibrosis was established by intratracheal injection of bleomycin (5 mg/kg). Mouse received anti-KL-6 antibody (20 ug/day, once a day) from day 7 to 21 after bleomycin injection. The effects of anti-KL-6 antibody were evaluated by pathological examination, measuring hydroxyproline measurements in lung tissues, leukocyte counts in BALF and the expression of collagen type I and type III using qRT-PCR. The expression of profibrotic cytokine (transforming growth factor-β1, TGF-β1 ), antifibrotic cytokine (hepatocyte growth factor, HGF), and KL-6 in lung tissues were analyzed by ELISA. The apoptosis of epithelial cell was examined by TUNEL staining. Results : Anti-KL-6 antibody significantly reduced the number of alveolar inflammatory leukocytes (total and differential counts) in BALF of mice with bleomycin-induced pulmonary fibrosis as well as the content of hydroxyproline in the lung tissues. Treatment with anti-KL-6 antibody downregulated the expression of collagen type I, TGF-β1 and KL-6, upregulated the expression of HGF and inhibited the apoptosis of epithelial cells. Conclusions : These findings indicated the anti-KL-6 antibody may potentially be developed as a useful inhibitor of pulmonary fibrosis.